Partial milking of cattle in smallholder herds on the Accra plains. 1. some factors affecting daily partial milk yield and milk composition - Okantah, S.A. (Cambridge University Press, 1992)
Presents a study undertaken to measure the partial milk yields of cows, the composition of milk and some environmental factors that influence partial milk extracted under smallholder agropastoral management conditions on the Accra plains in Ghana. Daily partial milk yield of Sanga cows in 13 smallholder agropastoralist herds at two locations on the Accra plains was recorded through monthly sampling. Estimates of mean daily partial milk yield and milk compostion were computed from 1266 observations. The unadjusted mean daily partial milk yield and milk composition were computed from 1266 observations. The unadjusted mean daily partial milk yield was 875 (s.e. 11)g. The composition of milk: total solids (TS), fat (F) and solid-non-fat (SNF) were 131 (s.e. 14), 41(s.e.11) and 90(s.e.7) g/kg respectively. Least square estimate of mean daily partial milk yield were 808.2 and 462.4g with average s.e. of 41.8 for wet and dry season respectively. The wet and dry season differences in daily partial milk yield, TS and F were highly signficant (p<0.01). Seasonal difference in SNF was not significant. Lactation curve parameters for partially milked cows were also estimated. The implications of the results for milk production in sub-Saharan Africa were discussed.